COMPARATIVE CHARACTERISTIC OF MEANS OF AUTOMATED CHECK OF THE CORRECTNESS OF WRITING OF SQL REQUESTS - Z. V. Semenova; S. A. Lyubich; A. G Kuznetsov; P. A. Mal’tsev (Вестник СибАДИ)
The article presents an analysis of resources that can be used to test users who study the SQL language. Also, the article describes plan and result of the attack on web applications for learning the SQL language. There are some weaknesses of web applications in terms of their ability to verify the correctness of the compilation of SQL queries, which are also describes here. The conclusion deals with is made about the expediency of developing a specialized test system for verifying the correctness of writing SQL-queries.